An Investigation on Social Media Issues Using Big Data Analytics - Yemunarane, K; Hemavathi, D (International Journal of Computer Sciences and Engineering, 2025)
This paper describes how big data technologies are converging to offer a cost-effective delivery model social media based big data analytics. Social Media is a powerful technology to perform massive-scale and complex computing. It eliminates the need to maintain expensive computing hardware, dedicated space, and software. Massive growth in the scale of data or big data generated through social media has been observed. Addressing big data is a challenging and time demanding task that requires a large computational infrastructure to ensure successful data processing and analysis. In this paper the relationship between big data and social media, the classification of big data and the scope of big data analytics are discussed